Opioid Intratekal pada Enhanced Recovery After Surgery (Eras) - Sudadi; Loho, Irvan Revaldi; Wisudarti, Calcarina Fitriani Retno (Jurnal Komplikasi Anestesi, 2023)
Enhanced Recovery After Surgery (ERAS) is a multidisciplinary protocol introduced for a faster and more effective recovery from elective surgery. The target of ERAS is early mobilization, early oral intake and a faster length of stay. Preoperative ERAS recommends optimizing the patient's clinical condition, smoking cessation, minimizing fasting and drinking clear, carbohydrate-rich fluids up to 2 hours before surgery, reducing patient anxiety, and PONV prophylaxis. Intraoperatively, ERAS recommends the use of multimodal analgesia, maintenance of normothermia, and goal-directed fluid therapy. Postoperatively, ERAS recommends multimodal analgesia so that patients can mobilize early and eat early. Intrathecal opioid therapy can be an option in achieving the goals of ERAS. Optimal use of opioids is one of the factors that influence effectiveness in patients with the ERAS protocol.